Resolvin D1 limits 5-lipoxygenase nuclear localization and leukotriene B4 synthesis by inhibiting a calcium-activated kinase pathway - Fredman, Gabrielle; Ozcan, Lale; Spolitu, Stefano; Hellmann, Jason; Spite, Matthew; Backs, Johannes; Tabas, Ira (Proceedings of the National Academy of Sciences of the United States of America, 2014)
Imbalances between proinflammatory and proresolving mediators can lead to chronic inflammatory diseases. The balance of arachidonic acid-derived mediators in leukocytes is thought to be achieved through intracellular localization of 5-lipoxygenase (5-LOX): nuclear 5-LOX favors the biosynthesis of proinflammatory leukotriene B4 (LTB4), whereas, in theory, cytoplasmic 5-LOX could favor the biosynthesis of proresolving lipoxin A4 (LXA4). This balance is shifted in favor of LXA4 by resolvin D1 (RvD1), a specialized proresolving mediator derived from docosahexaenoic acid, but the mechanism is not known. Here we report a new pathway through which RvD1 promotes nuclear exclusion of 5-LOX and thereby suppresses LTB4 and enhances LXA4 in macrophages. RvD1, by activating its receptor formyl peptide receptor2/lipoxin A4 receptor, suppresses cytosolic calcium and decreases activation of the calcium-sensitive kinase calcium-calmodulin-dependent protein kinase II (CaMKII). CaMKII inhibition suppresses activation P38 and mitogen-activated protein kinase-activated protein kinase 2 kinases, which reduces Ser271 phosphorylation of 5-LOX and shifts 5-LOX from the nucleus to the cytoplasm. As such, RvD1’s ability to decrease nuclear 5-LOX and the LTB4:LXA4 ratio in vitro and in vivo was mimicked by macrophages lacking CaMKII or expressing S271A-5-LOX. These findings provide mechanistic insight into how a specialized proresolving mediator from the docosahexaenoic acid pathway shifts the balance toward resolution in the arachidonic acid pathway. Knowledge of this mechanism may provide new strategies for promoting inflammation resolution in chronic inflammatory diseases.
Gesehen am 14.07.2020